pk000287: Spanish anti-fascist war 1936-39. Las milicias de la cultura. - Ministry of Public Instruction of the Spanish Republican Government; Marx Memorial Library; Leeds postcards
"Prentbriefkaart in kleur voorstellend een openliggend boek met opschrift 'Cartilla escolar antifascista' en een geweer, gemaakt naar aanleiding van de Spaanse Burgeroorlog. FULL TEXT AVAILABLE AT AMSAB-ISH"